Policy Advice in Multi-Level Governance Systems: Sub-National Policy Analysts and Analysis - Howlett, Michael (International review of public administration, 2009)
Despite the existence of a large body of literature on policy analysis, empirical studies of the work of policy analysts are rare, and in the case of analysts working at the sub-national level in multi-level governance systems, virtually non-existent. Many observers decry the lack of even such basic data as how many policy analysts work in sub-national government, on what subjects, and with what effect. This is true in many countries, for example, the U.S., Germany, and Canada, all federal systems with extensive sub-national governments but where what little empirical work exists focuses on government at the national level. In most cases, in justifying their observations and conclusions observers rely on only one or two quite dated works, on very partial survey results, or on anecdotal case studies and interview research. This article reports the findings of a 2008-2009 survey aimed specifically at examining the background and training of provincial policy analysts in Canada, the types of techniques they employ in their jobs, and what they do in their work on a day-by-day basis. The resulting profile of sub-national policy analysts presented here reveals several substantial differences between analysts working for national governments and their sub-national counterparts, with important implications for training and for the ability of nations to accomplish their long-term policy goals.